Exoplanet science with SPIRou: near-infrared precision velocimetry and spectropolarimetry - Moutou, Claire; Donati, Jean-François; Debras, Florian (Comptes Rendus. Physique)
High-precision radial-velocity measurements in the near-infrared allow one to search for exoplanet signals around the lowest-mass stars, including young ones. Because these stars can be among the most active ones, it is essential to characterize their magnetic activity. SPIRou, installed at the Canada–France–Hawai’i telescope, was designed to explore such planetary systems and characterize their properties. With a wide spectral range and large resolving power, SPIRou is also optimized for transmission spectroscopy and for investigating the chemical composition of exoplanetary atmospheres.